2018
DOI: 10.1177/0013916518807274
|View full text |Cite
|
Sign up to set email alerts
|

Window View to the Sky as a Restorative Resource for Residents in Densely Populated Cities

Abstract: We investigated the extent to which the amount of sky and other contents affect expectations that window views will support psychological restoration in an urban context. The study involved 102 digital view images across which the amount of sky and other contents were varied systematically through manipulation of variables relevant to urban densification. University students ( N = 212) rated images on restorative quality (being away, fascination), restoration likelihood, or preference. We aggregated the rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 60 publications
4
56
1
1
Order By: Relevance
“…Evidence from a few studies has suggested that natural light and views provided by windows, affected by window size, can influence perceptions of both room size and crowding (Butler & Steuerwald, 1991;Ne'eman & Hopkinson, 1970;Schiffenbauer et al, 1977). Any window view is preferred over no view (Collins, 1975), and expanded window views afforded by higher floor level were found to reduce perceptions of crowding (Schiffenbauer et al, 1977) and result in higher restorative quality ratings (Masoudinejad & Hartig, 2018). College students perceived dormitory rooms that received more natural light as less crowded than darker rooms (Baum & Davis, 1976;Schiffenbauer et al, 1977).…”
Section: Interior Density Perceived Crowding and Residential Designmentioning
confidence: 99%
“…Evidence from a few studies has suggested that natural light and views provided by windows, affected by window size, can influence perceptions of both room size and crowding (Butler & Steuerwald, 1991;Ne'eman & Hopkinson, 1970;Schiffenbauer et al, 1977). Any window view is preferred over no view (Collins, 1975), and expanded window views afforded by higher floor level were found to reduce perceptions of crowding (Schiffenbauer et al, 1977) and result in higher restorative quality ratings (Masoudinejad & Hartig, 2018). College students perceived dormitory rooms that received more natural light as less crowded than darker rooms (Baum & Davis, 1976;Schiffenbauer et al, 1977).…”
Section: Interior Density Perceived Crowding and Residential Designmentioning
confidence: 99%
“…Several studies have indicated that seeing greenness though windows may promote health and well-being by providing micro-restorative episodes that promote healing [31][32][33][34], facilitate psychological restoration [35], increase recovery from stressful events [36], and improve affective and functional well-being [37]. Furthermore, being able to enjoy green window views has been seen to positively affect an individual's cognitive capacity [38] increase life- [39] and jobsatisfaction [40], and promote fascination and a sense of being away from everyday life [41]. In a recent study, Dzhambov et al (2020) [9] reported that university students in Bulgaria, who were forced to self-isolate at home because of the COVID-19 restrictions, but had abundant greenery visible from their home windows or in the neighborhood, showed both reduced symptoms and rates of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Some psychological benefits have been shown to occur simply through a pleasant view of a park from a window. 31 , 32 Furthermore, loneliness may also be reduced for a person who is housebound (e.g. due to disability or a long-term health condition) as a result of potentially greater collective levels of efficacy, cohesion and optimism spilling over from positive neighbourly interactions supported by green space.…”
Section: Introductionmentioning
confidence: 99%